Comparative research on Korean jangseungs and Lithuanian religious monuments - Šiaučiūnas-Kačinskas, Martynas (Acta Orientalia Vilnensia, 2008)
Kyung Hee UniversityThe research deals with Korean jangseungs and Lithuanian religious monuments, which include various kinds of Christian crosses, chapels, chapel pillars, and roofed pillars. The latter two are sometimes referred to as chapel pillars and roofed pillars (or collectively, decorative crosses) in English. This research focuses on chapel- pillars and roofed pillarsdecorative crosses only. Such monuments are seen quite often all over both countries, and they attract the eyes of tourists visiting the countries. The shape of the monuments is quite different: Korean jangseungs are pillars with a human-shaped body and the Lithuanian monuments are pillars having many Christian symbols. After deeper analysis, it can be concluded that both monuments are closely related by their functions. They are erected at the boundaries of villages, in the most important places in villages, near roads and dangerous places, etc. These monuments from both countries are supposed to protect the sphere of human life and ensure prosperity, health, a good harvest, etc. They also have strong ties with the veneration of ancestors, still very vivid in these two countries. And since both monuments are pillars, they have deep relations with the world pillar (axis mundi): a belief widely known throughout the world.